Genetic redundancy and persistence of plasmid-mediated trimethoprim/sulfamethoxazole resistant effluent and stream water Escherichia coli. (15th October 2016) - Suhartono, Suhartono; Savin, Mary; Gbur, Edward E.
Abstract: Antibiotic resistant bacteria may persist in effluent receiving surface water in the presence of low (sub-inhibitory) antibiotic concentrations if the bacteria possess multiple genes encoding resistance to the same antibiotic. This redundancy of antibiotic resistance genes may occur in plasmids harboring conjugation and mobilization ( mob ) and integrase ( intI ) genes. Plasmids extracted from 76 sulfamethoxazole-trimethoprim resistant Escherichia coli originally isolated from effluent and an effluent-receiving stream were used as DNA template to identify sulfamethoxazole ( sul ) and trimethoprim ( dfr ) resistances genes plus detect the presence of intI and mob genes using PCR. Sulfamethoxazole and trimethoprim resistance was plasmid-mediated with three sul ( sul1, sul2 and sul3 genes) and four dfr genes ( dfrA12, dfrA8, dfrA17, and dfrA1 gene) the most prevalently detected. Approximately half of the plasmids carried class 1 and/or 2 integron and, although unrelated, half were also transmissible. Sampling site in relationship to effluent input significantly affected the number of intI and mob but not the number of sul and dfr genes. In the presence of low (sub-inhibitory) sulfamethoxazole concentration, isolates persisted regardless of integron and mobilization gene designation, whereas in the presence of trimethoprim, the presence of both integron and mobilization genes made isolates less persistent than in the absence of both or the presence of a gene from either group individually. Regardless, isolates persisted in large concentrations throughout the experiment. Treated effluent containing antibiotic resistant bacteria may be an important source of integrase and mobilization genes into the stream environment. Sulfamethoxazole-trimethoprim resistant bacteria may have a high degree of genetic redundancy and diversity carrying resistance to each antibiotic, although the role of integrase and mobilization genes towards persistence is unclear. Graphical abstract: Highlights: Plasmids with three sul and four dfr genes were the most prevalently detected. Plasmids possessed redundancy in sul and dfr resistance genes. Half of the plasmids had class 1 and/or 2 integron and half were transmissible. intI-mob genes had no effect on Escherichia coli persistence with sulfamethoxazole. intI-mob genes affected E. coli persistence in sub-inhibitory trimethoprim.